DNA methylation in fish of the cichlid family: A systematic review - Elias Welengane; Luan Felipe da Silva Frade; Luana Beatriz Sales Pinon; Carlos Eduardo Vasconcelos dos Santos; Adauto Lima Cardoso; Luís Adriano Santos do Nascimento; Renata Coelho Rodrigues Noronha (Heliyon)
Cichlidae is considered one of the most diverse families of freshwater fish in the world. The representatives of this group are known for their ecological and behavioral diversity. DNA methylation is an epigenetic process that involves the addition of methyl groups to DNA, affecting gene expression without altering the DNA sequence. This process has been widely studied in various organisms. The occurrence of abnormal DNA methylation events in Cichlidae may play an important role in these fish's adaptation to different environments. This article presents a review of DNA methylation in fish of this family. For this purpose, a systematic approach was used to search for relevant research in three academic databases: ScienceDirect, Scopus, and Web of Science. Initially, 50 articles were selected based on inclusion criteria, of which 22 were included in this review. This process allowed the identification of the most relevant and high-quality studies on the topic. From the 22 selected articles, a keyword co-occurrence visualization map was created, making it possible to investigate the current state of knowledge about DNA methylation in Cichlidae. The review highlights that DNA methylation is crucial for these fish's adaptation to different environments, influencing gene expression and behavior. Environmental factors, such as temperature, pH, and oxygen, affect this epigenetic modification. Furthermore, DNA methylation can also be impacted by exposure to toxic substances, which may compromise the health and survival of Cichlidae. This review allows understanding the implications of these studies for the conservation and management of these species, as it provides insights into how fish adapt to environmental changes and the risks associated with pollution, as well as providing information for future research.